Macroporous Silica Foams Fabricated via Soft Colloid Templating. Issue 4 (26th February 2022) - Bergman, Maxime J.; García‐Astrain, Clara; Fuchs, Nathan; Manne, Kalpana; Yazhgur, Pavel; Froufe‐Pérez, Luis S.; Liz‐Marzán, Luis M.; Scheffold, Frank
Abstract: Macroporous materials with controlled pore sizes are of high scientific and technological interest, due to their low specific weight, as well as unique acoustic, thermal, or optical properties. Solid foams made of titania, silica, or silicon, as representative materials, have been previously obtained with several hundred nanometer pore sizes, by using sacrificial templates such as spherical emulsion droplets or colloidal particles. Macroporous structures in particular are excellent candidates as photonic materials with applications in structural coloration and photonic bandgap devices. However, whereas using spherical building blocks as templates may provide tight control over pore shape and size, it results in materials with an often unfavorable local topology. Templating dry‐foam or compressed‐emulsion structures appear as attractive alternatives, but have not been demonstrated so far for submicron pore sizes. Herein, the use of soft, flexible microgel colloids decorated with silica nanoparticles as templates of macroporous foams is reported. These purposely synthesized core–shell colloids are assembled at ultra‐high effective volume fractions by centrifuging and thermal swelling, thereby resulting in uniform disordered materials with facetted pores, mimicking dry foams. After removal of the polymer component via calcination, lightweight pure silica structures are obtained with a well‐defined cellular or network topology. Abstract : Macroporous foams are light‐weight structures with large, open pores. Disordered foams are candidates for amorphous photonic materials, yielding angle‐independent structural color. In this study, designer silica decorated microgels are self‐assembled into disordered macroporous foams with monodisperse pore size. Synthesis parameters directly impacted foam properties. The results encourage facile production of tailor‐made disordered macroporous foams.